Exploratory study of patients’ and carers’ preferences for postdischarge surgical wound monitoring using survey and interviews - Keith Wilson; Nigel Westwood; Catherine Wloch; Pauline Harrington; Luke J Rogers; Judith Tanner; Gavin Murphy; Colin S Brown; Jeremy Dearling; Ricky Vaja; Melissa Rochon; Lyn Brierley Jones (BMJ Open)
Objectives To explore patients’ and carers’ preferences for postdischarge surgical wound monitoring.Design Explanatory mixed methods study with an online survey followed by online interviews.Setting The online survey was distributed via the Cardiothoracic Interdisciplinary Research Network and cardiac surgery patient and public involvement groups in London and Leicester, UK. Participants were invited to share the survey link with other patients and carers. Interviewees were recruited through the survey.Participants Seventy participants completed the survey: 74% patients and 26% carers. A range of ages, sex, ethnicities and geographical locations were represented. Six survey patient participants volunteered to be interviewed.Findings Themes identified were the impact on patients of having a surgical site infection, patients’ preferences for postdischarge surgical wound follow-up, access to specialist support, wound monitoring using digital technology and receiving information from the hospital about wounds and wound care. Interviewees described feeling isolated after discharge from hospital and 10% of survey patient respondents, including four of the six interviewees, reported hospital readmissions. Survey respondents’ preferred routes for providing hospitals with wound information were over the telephone (30%), emails (24%), text messages (16%) and photos sent securely (14%). All six interviewees’ preference was for digital approaches using images. Survey respondents were least likely (50%) to reply to questionnaires that required software to be downloaded and installed. Interviewees considered digital wound monitoring to be convenient and the best use of patient and staff resources. A new theme was identified where patients wanted to become more involved in treating their surgical wounds at home.Conclusion Experiences described by participants suggests there is a need to improve post-discharge wound monitoring. A new approach should be proactive, ongoing and provide easy access to healthcare services. Digital surgical wound monitoring offers these benefits and is acceptable to patients.Trial registration number ISRCTN13950775; Post-results.